2017
DOI: 10.1371/journal.pone.0179057
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the dynamics of terrorism events with multiple-discipline datasets and machine learning approach

Abstract: Terror events can cause profound consequences for the whole society. Finding out the regularity of terrorist attacks has important meaning for the global counter-terrorism strategy. In the present study, we demonstrate a novel method using relatively popular and robust machine learning methods to simulate the risk of terrorist attacks at a global scale based on multiple resources, long time series and globally distributed datasets. Historical data from 1970 to 2015 was adopted to train and evaluate machine lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 28 publications
(24 reference statements)
0
27
0
1
Order By: Relevance
“…SVM, Naïve Bayes, and logistic regression were used, and they demonstrated an accuracy of up to 78%. In [19], Ding et al used machine learning methods (NNET, SVM, and Random Forest) to simulate the risk of terrorist attacks. e model was able to predict the places where terrorist events might occur with a success rate of 96%.…”
Section: Related Workmentioning
confidence: 99%
“…SVM, Naïve Bayes, and logistic regression were used, and they demonstrated an accuracy of up to 78%. In [19], Ding et al used machine learning methods (NNET, SVM, and Random Forest) to simulate the risk of terrorist attacks. e model was able to predict the places where terrorist events might occur with a success rate of 96%.…”
Section: Related Workmentioning
confidence: 99%
“…This approach of using data-driven predictive models to predict malicious behaviour is not new and current models using machine learning technologies have a high degree of theoretical accuracy in detecting terrorist behaviour (Salih et al 2017;RAND National Security Research Division 2005;Li et al 2018;Ding et al 2017;Schneider et al 2011). With accessibility to more data for machine learning and iterative improvements, these terrorist focussed models are likely to improve over time and the learnings from these models are likely to be useful inputs into an AI treachery model.…”
Section: Artificial Intelligence Treachery Threat Modelmentioning
confidence: 99%
“…This method used prospective space-time scan statistics and could detect outbreaks of terrorist events at an early stage. Ding et al (2017) demonstrated a deep learning method to evaluate risks of terrorist attacks on a global scale based on GTD dataset and other multiple resources datasets. The method performed well in predicting the terrorism incidents with a precision of 96.6%.…”
Section: Simulating and Forecasting The Geopolitical Eventsmentioning
confidence: 99%